Epidemiological Study of Road Traffic Accident Cases Attending Tertiary Care Hospital in Bhopal, Madhya Pradesh - Neeraj Khare; Sanjay K Gupta; Atul Varshney; AV Athavale (Medsci Publications, 2012)
Background: Road Traffic Accident (RTA) is one among the top five causes of morbidity and mortality in South-East Asian countries including India. 1 Its socioeconomic repercussions are a matter of great concern. Efficient addressing of the issue requires quality information on different causative factors. Objectives- What are different epidemiological determinants of RTA in Bhopal MP and examine the factors associated with RTA. Methodology: Study Design: retrospective observational. Setting: Study was performed in a tertiary healthcare delivery institute in Bhopal MP. Participants: All RTA cases coming to Emergency of Peoples hospital. Study Periods: 2009 JAN to OCT 2011. Study Variables: Demographic, human, vehicular, environmental and time factors. Results: In studied cases most of them were males 1047 (82.5%) and 16-31 years of age 647 (51%). Most common time duration of occurrence of RTA was 6PM to 12 PM 783(62%), most common injury after RTA was head injury 808 (64%), and most common cause of RTA according to type of vehicle was motor cycle (Two wheelers) 929(73%).The RTA cases according to place of occurrence more common on Ayodhya bypass Road 463 (37%) and least common on Raisen Road 91(7%). RTA cases according to time taken to reach hospital were less than 30 minutes in more of the cases 774(61%). Overall mortality among RTA cases was 40 (3.15%). Conclusion: Most of the factors responsible for RTA and its fatal consequences are preventable. A comprehensive multi-programme approach can mitigate most of them.